Portugal and the Dominican Republic: From an innovative ‘Portuguese Plan’ for Dominican tourism (1995-1997) to current reality (2016) - Mangorrinha, Jorge; Universidade Lusófona de Humanidades e Tecnologias (2018)
Twenty years ago, we were the first Portuguese hands-on team abroad to carry out a Tourism planning project, and in two decades the Dominican Republic has transformed itself tourism-wise and has been a preferred destination of the Portuguese ever since. It can be seen that tourism planning has a very close relationship with history and culture; furthermore, history is essential so that in the present, pathways for the future in global tourism may be drawn and in particular in the Ibero-American area, in the light of the network of possible exchanges, circuits and routes between both sides of the Atlantic, in current and future times.